Trattamento delle fratture periprotesiche dell’anca: sintesi vs revisione - Colombi, A.; Castelli, C.C. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC HIP FRACTURE: ORIF VS REVISION SURGERYFemoral periprosthetic fractures in hip surgery still represent a difficult surgical procedure and a secure optimaltreatment has not been found yet. Great help is provided by the development of commonly used classifications such asthe Vancouver classification and the recent Unified Classification System (UCS), which introduce clearer fracturepatterns with the respective surgical indications. The most discussed pattern is related to category B of bothclassifications in which, despite the use of established treatment paradigms, results are poor or otherwiseunpredictable. This study reviews the literature related to the analysis of fractures and its following treatment.